Countries must safeguard children’s rights from climate change and environmental damage - UN committee - Amnesty International (Amnesty International, 2023)
UN Committee on the Rights of the Child has concluded that countries must urgently implement measures to address the damage and threat to children’s rights from climate change and environmental degradation.
Keywords: 2023-08 August; Child Rights

Crise climatique. Les États doivent protéger les droits des enfants du changement climatique et des dégradations de l’environnement - Comité des Nations unies - Amnesty International (Amnesty International, 2023)
Les enfants sont parmi les personnes les plus vulnérables aux conséquences du changement climatique et des dégradations de l’environnement dans le monde.
Keywords: 2023-08 August